Application of Solid Waste Artificial Substrate Improvement Technology in Mine Ecological Restoration - Wang, Na; Chen, Weiwei; Xia, Longfei (International Journal of Natural Resources and Environmental Studies, 2025)
Soil degradation is one of the main challenges affecting the success of ecological restoration in mining areas. Mine soils often face issues such as nutrient depletion, acidification, and compaction, which hinder vegetation recovery and slow down the ecological restoration process. This paper reviews the basic composition of solid waste artificial substrates, compares the advantages and disadvantages of different types of solid waste and their applicable scopes, and discusses the application of solid waste artificial substrates in mine soil improvement. Furthermore, the development of solid waste artificial substrates is forecasted, aiming to provide solutions for the resource utilization of solid waste in mine ecological restoration.